2020
DOI: 10.1021/acsomega.0c01474
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Synthesis of the C1–C16 Fragment of the Purported Structure of Formosalide B

Abstract: The first stereoselective synthesis of the C1−C16 fragment possessing stereo-enriched fully substituted tetrahydropyran (THP) along with tetrahydrofuran (THF) rings of the proposed structure of formosalide B is described in 12 longest linear steps with 22% overall yield, starting from two cheap and commercially available 1,5-pentanediol and L-glutamic acid, following a convergent approach. The key steps involve in this synthesis are Horner−Wadsworth−Emmons reaction, Sharpless asymmetric dihydroxylation, and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Thorough NMR studies allowed only the relative configuration within each of the three color‐coded stereoclusters to be determined but could not establish their mutual relationships nor their absolute configuration; [9] eight possible combinations (four diastereomers and their respective enantiomers) have hence to be considered. Because of the flexibility of the macrocycle and the lack of crystallographic data, synthesis is arguably the most definitive way to the answer [12] . A priori, such a project must be capable of producing any conceivable isomer [13] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thorough NMR studies allowed only the relative configuration within each of the three color‐coded stereoclusters to be determined but could not establish their mutual relationships nor their absolute configuration; [9] eight possible combinations (four diastereomers and their respective enantiomers) have hence to be considered. Because of the flexibility of the macrocycle and the lack of crystallographic data, synthesis is arguably the most definitive way to the answer [12] . A priori, such a project must be capable of producing any conceivable isomer [13] .…”
Section: Methodsmentioning
confidence: 99%
“…Because of the flexibility of the macrocycle and the lack of crystallographic data, synthesis is arguably the most definitive way to the answer. [12] Ap riori, such ap roject must be capable of producing any conceivable isomer. [13] We reasoned that the blueprint sketched in Scheme 1qualifies for such an "integral approach": [14] specifically,t he late-stage attachment of the polyene side chain seemed advisable for the sake of convergence and for stability reasons alike.C onvergence is also imperative for the assembly of the eight diastereomeric macrocyclic cores that are potentially needed.…”
mentioning
confidence: 99%
“…Lu and his co-researchers reported the total synthesis of formosalide A in recent times. However, in 2020, Gajula et al [ 126 ] reported the total synthesis of C1-C16 fragment of formosalide B. The synthesis began with the reduction of lactone 305 by using DIBAL-H in the presence of dichloromethane followed by Wittig olefination and treatment with mesylate chloride in the presence of trimethylamine, dimethylaminopyridine and dichloromethane, which gave mesylate ester 306 in 95% yield.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The required trans-disubstituted tetrahydrofuran ring 68 was prepared by stereoselective cobalt-catalyzed oxidative cyclization of bishomoallylic alcohol 69, with excellent yield and selectivity (Scheme 12). Mohapatra and co-workers have also reported a stereoselective synthesis of the C1-C16 fragment of formosalide B [52]. A one-pot Sharpless asymmetric dihydroxylation of α,β-unsaturated ester 74, followed by intramolecular S N 2 displacement, produced the desired trans-tetrahydrofuran 75 with a high 88% yield and total stereoselectivity (Scheme 14).…”
Section: Chagosensinementioning
confidence: 99%